Initial experience of 980‐nm diode laser treatment for recurrent non‐muscle‐invasive bladder cancer - Hideo Fukuhara; Yusei Hamada; Syo Shimasaki; Ryohei Iga; Kaya Atagi; Ryu Shigehisa; Yuhi Ota; Shinkuro Yamamoto; Hiroto Osakabe; Tomoya Nao; Tsutomu Shimamoto; Satosi Fukata; et al. (IJU Case Reports)
Introduction Laser ablation using a 980‐nm wavelength diode laser, which is a new‐generation laser, for recurrent bladder cancer is known to have a lower incidence of complications and recurrence than conventional transurethral resection of bladder tumor surgery. This is the first study to report the use of 980‐nm diode laser ablation for recurrent non‐muscle‐invasive bladder cancer in Japan. Case presentation A 73‐year‐old man underwent transurethral laser ablation for the treatment of recurrent non‐muscle‐invasive bladder cancer. Laser irradiation was performed using LEONARDO DUAL (diode laser/980‐nm wavelength) and a 400‐μm BARE laser fiber. Pathological evaluation indicated low‐grade urothelial carcinoma, pTa. The patient was discharged on the second postoperative day with no perioperative or postoperative complications. Conclusion This case suggests the potential of transurethral laser ablation for treating recurrent non‐muscle‐invasive bladder cancer.